Provenance of Permian-Triassic Gondwana Sequence units accreted to the Banda Arc in the Timor region: Constraints from zircon U-Pb and Hf isotopes - Spencer, Christopher; Harris, R.; Major, J. (2015)
Analysis of zircons from Australian affinity Permian-Triassic units of the Timor region yield age distributions with large age peaks at 230-400. Ma and 1750-1900. Ma, which are similar to zircon age spectra found in rocks from NE Australia and crustal fragments now found in Tibet and SE Asia. It is likely that these terranes, which are now widely separated, were once part of the northern edge of Gondwana near what is now the northern margin of Australia. The Cimmerian Block rifted from Gondwana in the Early Permian during the initial formation of the Neo-Tethys Ocean. The zircon age spectra of the Gondwana Sequence of NE Australia and in the Timor region are most similar to the terranes of northern Tibet and Malaysia, further substantiating a similar tectonic affinity. A large 1750-1900. Ma zircon peak is also very common in other terranes in SE Asia.Hf analysis of zircon from the Aileu Complex in Timor and Kisar Islands shows a bimodal distribution (both radiogenically enriched and depleted) in the Gondwana Sequence at ~. 300. Ma. The magmatic event from which these zircons were derived was likely bimodal (i.e. mafic and felsic). This is substantiated by the presence of Permian mafic and felsic rocks interlayered with the sandstone used in this study. Similar rock types and isotopic signatures are also found in Permian-Triassic igneous units throughout the Cimmerian continental block.The Permian-Triassic rocks of the Timor region fill syn-rift intra-cratonic basins that successfully rifted in the Jurassic to form the NW margin of Australia. This passive continental margin first entered the Sunda Trench in the Timor region at around 7-8. Ma causing the Permo-Triassic rocks to accrete to the edge of the Asian Plate and emerge as a series of mountainous islands in the young Banda collision zone. Eventually, the Australian continental margin will collide with the southern edge of the Asian plate and these Gondwanan terranes will rejoin.